Descripción litroestratigráfica y aspectos sedimentológicos de las unidades - Rodríguez, S.; Falces, S.; Arribas, M.E.; Peña, J.A. De la; Comas-Rengifo, M.J.; Moreno-Eiris, E. (Coloquios de Paleontología, 1992)
Sin resumen